(untitled) (Andamios, Revista de Investigación Social, 2014)
In our paper we tackle the topic of the knowledge of Mexican Spanish vocabulary through several types of dictionaries registering it. We make an historical overview recalling the impact of Spanish on the autochthonous people, as well as some remarks on the influence of the Castillian norm, as the leading norm, on Mexican Spanish. We also offer points of analysis for the knowledge of the privative and we analyze the theoretical tendencies of actual lexicography in registering Mexican Spanish.